Recasting Analytic Philosophy on the Problem of Evil - Mintoff, Joe (Sophia, 2013)
In his recent book, A Frightening Love: Recasting the Problem of Evil, Andrew Gleeson challenges a certain conception of justification assumed in mainstream analytic philosophy and argues that analytic philosophy is ill-suited to deal with the most pressing, existential, form of the problem of evil. In this article I examine some aspects of that challenge.